A RESEARCH ON THE PHYSICAL EDUCATION AND SPORTS TEACHERS’ LEISURE ATTITUDE LEVEL: ADANA SAMPLE - Kepoglu, Abdurrahman; Musa, Mihriay; Bayansalduz, Mehmet; Yanar, Senol; Demirtas, Ömercan (Acta Scientiae et Intellectus, 2024)
The aim of this study is to investigate the leisure time attitude levels of physical education and sports teachers working in Adana Province. The quantitative research design, one of the research designs, was used in the study. The universe of the study consists of physical education and sports teachers working in Adana. The sample of the study consists of 58 male 42 female 100 physical education and sports teachers who teach physical education and sports in the Adana region. Personal information form developed by the researcher, and “Leisure Attitude Scale” adapted into Turkish by Akgul and Gurbuz (2011) were used for data collection. In analyzing the data, Mann-Whitney U Test at 0.05 significance level, Kruskal Wallis Test, the Correlation at 0.01 significance level, and Regression analysis at 0.05 significance level were used. As a result of the study, it was determined that individuals who work as physical education and sports teachers in Adana Province have high leisure time attitudes. There is no difference in leisure time attitude levels according to gender, age groups, duration of teaching, the institution where they work, and the activities that individuals do outside of working hours.